PELATIHAN STORYTELLING DALAM BAHASA INGGRIS UNTUK SISWA SMA KATOLIK SINT CAROLUS KUPANG - Antonia Tefa; Chamelya Vivi Crystanty Sene; Rozita Yusniaty Lodo; Mansuetus Mola; Agnes O. Manek (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
The United Kingdom storytelling training is an effort made to increase the interest and storytelling skills of Sint Carolus Kupang Catholic High School (SMA) students. This school has difficulty managing United Kingdom storytelling activities as one of its extracurricular activities due to the lack of competent Human Resources (HR) so that this activity is not in great demand by students. Storytelling is the activity of telling an event in an interactive way. The activity began by providing an explanation of storytelling and the ability to speak United Kingdom. After that, the speaker practiced United Kingdom storytelling directly in front of the participants and ended with the speaker inviting participants to participate in the storytelling practice by demonstrating storytelling in front of the class. It is hoped that this storytelling training can motivate students to improve their storytelling skills in United Kingdom and also motivate teaching staff in managing and presenting teaching materials for United Kingdom extracurriculars, especially storytelling